Evaluation of Public Transportation and Its Ability to be Used on Bani Walid-Tripoli Road - Hamza M. Elghatas; Yusef A. Sammas (المجلة الأفروآسيوية للبحث العلمي, 2024)
This study initially addresses the public transport system in the city of Bani Walid and its existing transportation issues. Next, an assessment was conducted to evaluate the quality of transit service in Bani Walid, including factors such as the availability of transit options, the level of comfort provided, and the overall convenience of the service. To achieve this objective, the initial step involved assessing the availability of transit based on factors such as the frequency of service, operating hours, and geographical coverage. Public transit is frequently portrayed as a crucial element in the development of sustainable cities. On the other hand, the social, economic, and environmental effects of transport are seen as important problems that might threaten the long-term viability of cities and regions. This report gives an assessment of the effectiveness of public transport on the Bani Walid-Tripoli Road. The study aimed to examine the mode choice behavior of travelers while deciding between using a car or bus. It also sought to identify the factors that influence travelers to switch from using their cars to using public transport. Precise enquiries were made to determine the reasons behind the preference for the car over the bus.